A diffusion problem with gradient constraint depending on the temperature - Azevedo, Assis (2010)
We consider a system of a variational inequality with gradient constraint depending on the temperature, coupled with the heat equation. We prove existence of solution of this system by approximating it by a system of equations and using a fixed point argument.